Unique class encryption (UCE) substitution boxes (S-Boxes) using mysterious Quranic for block ciphers in ICT security - Shamsudin, Ahmad Faizul; Suhaimi, Mohd Adam; Makarin, Rusydi Hasan; Jaafar, Abi Dzar (2010)
Unforeseen attacks on ICT systems incurred billions of dollars of losses to public and private communities. The current parametric encryption algorithms suffer the unconventional and paranormal attacks. A search for a new paradigm against the unforeseen and paranormal attacks lead to an invention called Unique Class Encryption (UCE) that is based on the non-parametric and mysterious verses of the Al-Quran.Earlier, the Al-Muqatta’at based UCE was developed and tested in a Red-Hat cluster funded under IRPA and completed in 2006. The Al-Muqattaat UCE was patent filed in 2007. A block cipher is required as a medium to translate the non - parametric Al-Muqatta’at algorithm into a suite so that it can be an embedded system for FPGA chips. This would require the construction of substitution boxes (SBoxes) with the other non-parametric objects from Al-Muawwidzatain and Ayatul Qursi verses. It is a completed Type A research endowment fund project in August 2009. The approach was to construct bigger S-Boxes that have no algebraic relations. The random bijective 8-bit S-Boxes that used the nonparametric and non-deterministic components of the Al-Qura’an would transform the objects into specific values for the S-Box construction. Thus the vital component of the non-parametric UCE block ciphers, that are the S-Boxes were developed. About 13.5 million of 8-Bit S-Boxes were generated. The nonlinearity and differential uniformity tests by MIMOS Cyber-security Laboratory showed the standing of UCE S-Box to be equivalent to that of Khazad’s block ciphers. Collaborative research with MIMOS Cyber-security Laboratory are using the strong UCE S-Boxes to develop hybrid round functions and key distribution algorithms to construct the UCE block cipher. This on-going phase is conducted under Type B research endowment fund. In an envisaged pre-commercialization phase, the UCE block cipher would be implemented in FPGA chips. The potential use for the UCE encryption chips will be as embedded cryptographic system in VPN routers, gateways, computing machines and security device firmware.